Effect of remimazolam vs propofol in high-risk patients undergoing upper gastrointestinal endoscopy: a non-inferiority randomized controlled trial - Zhi Li; Daming Yuan; Yu Yu; Jie Xu; Weili Yang; Li Chen; Nanbo Luo (Trials, 2024)
Abstract Background Procedural sedation is essential for optimizing upper gastrointestinal endoscopy, particularly in high-risk patients with multiple underlying diseases. Respiratory and circulatory complications present significant challenges for procedural sedation in this population. This non-inferiority randomized controlled trial aims to investigate the safety and comfort of remimazolam compared to propofol for procedural sedation during upper gastrointestinal endoscopy in high-risk patients. Methods A total of 576 high-risk patients scheduled to undergo upper gastrointestinal endoscopy are planned to be enrolled in this study and randomly allocated to either the remimazolam or propofol group. The primary outcome measure is a composite endpoint, which includes (1) achieving a Modified Observer’s Alertness/Sedation scale (MOAA/S) score ≤ 3 before endoscope insertion, (2) successful completion of the endoscopic procedure, (3) the absence of significant respiratory instability during the endoscopy and treatment, and (4) the absence of significant circulatory instability during the examination. The noninferiority margin was 10%. Any adverse events (AEs) that occur will be reported. Discussion This trial aims to determine whether remimazolam is non-inferior to propofol for procedural sedation during upper gastrointestinal endoscopy in high-risk patients, regarding success rate, complication incidence, patient comfort, and satisfaction. Trial registration {2a and 2b} Chinese Clinical Trial Registry ClinicalTrials.gov ChiCTR2200066527. Registered on 7 December 2022.